Multi-beam optical phase array for long-range LiDAR and free-space data communication - Wu, Yunhan; Shao, Shuai; Li, Yixuan; Chen, Xiangzheng; Che, Dongbo; Chen, Jiayu; Du, Kunyang; Jiang, Ruitao; Huang, Xunqing; Kan, Dongping (Optics and laser technology, 2022)
•We present a control architecture for an actively phase-locked OPA, capable of steering a laser beam at speeds limited by the actuation bandwidth of electro-optic modulators.•A multi-beam steering device is proposed for light detection and ranging (LIDAR).•Optical wireless transmission with two-dimensional (2D) beam-steering using an optical phased array (OPA). The design of the transmitter and receiver device parameters allowed the error-free transmission of 8 Gbps data over a distance of 3 km. We present a multi-beam optical fiber phased array (OPA) with simultaneous light detection and ranging (LiDAR) and free-space optical communication (FSO) data transmission functions. The OPA component can achieve a stable phase and a high turning speed. First, the 55-element OPA is phase-locked through the stochastic parallel gradient descent (SPGD) algorithm to maintain the high light intensity of the main beam in real time. The OPA with a 5 × 11 beam array achieved a wide field of view (FOV) of 58°×32°, a single beam array steering angle of0.48°, and a steering speed of 40 MHz. Subsequently, this OPA was used to detect targets within a range of approximately 2 km, and we theoretically verified that two-dimensional coherent frequency-modulated continuous wave (FMCW) LiDAR could extract the target characteristics. In addition, a free-space optical communication link of up to 3 km was also demonstrated, with a data rate of 8 Gbps. The proposed system easily increases the array-to-MHz steering speed and yields a high-power output.